PEGylated Polypyrrole Nanoparticles Conjugating Gadolinium Chelates for Dual-Modal MRI/Photoacoustic Imaging Guided Photothermal Therapy of Cancer - Liang, Xiaolong; Li, Yanyan; Li, Xiaoda; Jing, Lijia; Deng, Zijian; Yue, Xiuli; Li, Changhui; Dai, Zhifei (Advanced functional materials, 2015)
Polypyrrole nanoparticles conjugating gadolinium chelates were successfully fabricated for dual‐modal magnetic resonance imaging (MRI) and photoacoustic imaging guided photothermal therapy of cancer, from a mixture of pyrrole and pyrrole‐1‐propanoic acid through a facile one‐step aqueous dispersion polymerization, followed by covalent attachment of gadolinium chelate, using polyethylene glycol as a linker. The obtained PEGylated polypyrrole nanoparticles conjugating gadolinium chelates (Gd‐PEG‐PPy NPs), sized around around 70 nm, exhibited a high T1 relaxivity coefficient of 10.61 L mm−1 s−1, more than twice as high as that of the relating free Gd3+ complex (4.2 L mm–1 s−1). After 24 h intravenous injection of Gd‐PEG‐PPy NPs, the tumor sites exhibited obvious enhancement in both T1‐weighted MRI intensity and photoacoustic signal compared with that before injection, indicating the efficient accumulation of Gd‐PEG‐PPy NPs due to the introduction of the PEG layer onto the particle surface. In addition, tumor growth could be effectively inhibited after treatment with Gd‐PEG‐PPy NPs in combination with near‐infrared laser irradiation. The passive targeting and high MRI/photoacoustic contrast capability of Gd‐PEG‐PPy NPs are quite favorable for precise cancer diagnosing and locating the tumor site to guide the external laser irradiation for photothermal ablation of tumors without damaging the surrounding healthy tissues. Therefore, Gd‐PEG‐PPy NPs may assist in better monitoring the therapeutic process, and contribute to developing more effective “personalized medicine,” showing great potential for cancer diagnosis and therapy. A theranostic agent with excellent physiological stability, strong NIR absorption, and high magnetization is fabricated from PEGylated polypyrrole nanoparticles conjugating gadolinium chelates (Gd‐PEG‐PPy NPs). The passive targeting and high MRI/photoacoustic contrast capability of Gd‐PEG‐PPy NPs are favorable for precise cancer diagnosing and locating tumor sites to guide external laser irradiation for photothermal ablation of tumors without damaging surrounding healthy tissue.